Kepemimpinan pendidikan islam di era 5.0: Menyatukan hikmah tradisi dan kecanggihan teknologi - Mardilla, Alifiya (Maliki Interdisciplinary Journal, 2025)
Society 5.0 offers new dynamics in the world of Islamic education, where cutting-edge technologies such as artificial intelligence and big data are integrated to form a human-centered civilization. In this landscape, Islamic educational leadership is challenged to harmonize the noble values of Islamic heritage with today’s technological advances. This article aims to explore how the character and role of Islamic educational leaders can transform in the digital age, as well as to develop strategies for shaping a leadership model that is responsive, innovative, and grounded in Islamic values. This research employs a qualitative approach using literature review as the basis for analysis. The findings indicate that contemporary Islamic educational leaders must possess digital literacy, a forward-thinking vision, and uphold the moral principles and classical wisdom of Islam. Therefore, Islamic educational leadership in the 5.0 era must serve as a bridge between traditional roots and the evolving challenges of the digital age.